Next-Generation Molecular Diagnostics Development by CRISPR/Cas Tool: Rapid Detection and Surveillance of Viral Disease Outbreaks - Srivastava, Sonal; Upadhyay, Dilip J.; Srivastava, Ashish (Frontiers in Molecular Biosciences, 2020)
Virus disease spread effortlessly mechanically or through minute insect vectors which are extremely challenging to avoid. Emergence and re-emergence of new viruses such as SARS-CoV-2, H1N1 influenza virus, Avian influenza virus, dengue virus, Citrus tristeza virus, Tomato yellow leaf curl virus, have paralyzed the economy of many countries. The cure for major viral diseases is not feasible; however, early detection and surveillance of the disease can obstruct their spread. Therefore, advances in the field of virus diagnosis and the development of new Point-of-care testing kits become necessary globally. CRISPR/ Cas is an emerging technology for gene editing and diagnostics development. Several rapid nucleic acid diagnostic kits have been developed and validated using Cas9, Cas12, and Cas13 proteins. This review summarises the CRISPR/Cas based next-generation molecular diagnostic techniques and portability of devices for field-based utilization.